Kepribadian Alif Fikri dalam Novel Ranah 3 Warna Karya Ahmad Fuadi - Putri, Tri Wahyuni; Nurizzati, Nurizzati; Tressyalina, Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This study aimed to describe the personality aspect Alif Fikri of the novel Ranah 3 Warna Works Ahmad Fuadi, which includes individualita, finalisme pseudo two principal thrust/superiorita, inferiority and compensation, social encouragement, lifestyle lietlinie, and creative self. Aspects of personality associated with penokohan.Jenis research is a qualitative study using descriptive analysis. Sources of this study is the novel Ranah 3 Warna work of Ahmad Fuadi, published by Gramedia Pustaka UtamaÂ  in 2011th, consisting of 473 pages. Data collection was done with the stage (1) read and understand the novel Ranah 3 Warna by marking parts of the story that describes the data, (2) inventory data on aspects of the main character's personality with the help of a data inventory format. Analyzing the data carried by steps (1) to describe the data, (2) inventory data, (3) analyzing data, and (4) make the conclusion. Based on the results of this study revealed that Alif Fikri has all the aspects of personality based on the concept of Alfred Adler. However, the most dominant is finalisme false, while the least is the nature of individuality.